Plant communities and environmental factors in the Guayana Highlands: monitoring for conservation under future climate change. Issue 4 (3rd July 2016) - Safont, Elisabet; Vegas-vilarrúbia, Teresa; Rull, Valentí; Holst, Bruce K.; Huber, Otto; Nozawa, Shingo; Vivas, Yuribia; Font, Xavier; Silva, Argelia
Abstract : The Guayana Highlands (GH) constitute a highly diverse, but relatively poorly studied Neotropical biome, comprised of ∼50 flat-topped mountain summits (called tepuis). Previous studies based on warming forecasts for the region suggested that an upward displacement of environmental conditions of 500–700 m could occur by 2100, potentially resulting in the extinction of c . 50% of its endemic flora due to total habitat loss. To assess the ecological responses of the species to climate change, and select the appropriate conservation measures, long-term monitoring of the GH plant communities will be necessary. In this study, the baseline state for future comparisons was established for the best explored tepui in terms of its flora, Roraima-tepui (2810 m), through a floristic characterization of its different vegetation types. We also identified the environmental gradients underlying the major plant communities, and assessed the effects of human activities on the chemistry of soils and water at three field camps. Our results yielded five main community types: three meadows, one shrubland, and one forest, with their corresponding diagnostic species. The herbaceous communities were mainly influenced by the presence of flat sandy soils, with varying flooding capacity. Shrublands and forests were characterized by irregular organic soils with very low pH. Finally, pH values below 3 were measured on an organic soil of a field camp, although further studies will be necessary to attribute this deviation to human activities.